The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/magnetochemistry9070167
|View full text |Cite
|
Sign up to set email alerts
|

Process-Gas-Influenced Anti-Site Disorder and Its Effects on Magnetic and Electronic Properties of Half-Metallic Sr2FeMoO6 Thin Films

Ekta Yadav,
Ketan S. Navale,
Gulloo L. Prajapati
et al.

Abstract: Anti-site disorder, arising due to the similar size of Fe and Mo ions in Sr2FeMoO6 (SFMO) double perovskites, hampers spintronic applicability by deteriorating the magnetic response of this double perovskite system. A higher degree of anti-site disorder can also completely destroy the half-metallicity of the SFMO system. To study the effects of different process gas conditions on the anti-site disorder, we have prepared a series of SFMO thin films on SrTiO3 (001) single-crystal substrate using a pulsed laser d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…With the increase in the background gas pressure, the Full Width at Half Maxima (FWHM) starts increasing. This reduced crystallinity for SFMO films grown in oxygen and nitrogen gases, is consistent with our earlier observations of effects arising due to anti-site disorder in these films [27]. temperature.…”
Section: Structural Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…With the increase in the background gas pressure, the Full Width at Half Maxima (FWHM) starts increasing. This reduced crystallinity for SFMO films grown in oxygen and nitrogen gases, is consistent with our earlier observations of effects arising due to anti-site disorder in these films [27]. temperature.…”
Section: Structural Propertiessupporting
confidence: 92%
“…Keeping the above-mentioned points in consideration, we have synthesized a series of SFMO thin films in different background conditions on LaAlO 3 -LAO (001) single-crystal substrate using Pulsed laser Deposition (PLD) technique. The depositions have been carried out in vacuum and in nitrogen and oxygen gases which varies the degree of cation ordering in SFMO films as per our earlier study [27]. Moreover, LAO is the best-suited substrate for the Raman spectroscopic studies on SFMO thin films.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the ionic radii of iron and niobium in a sixfold environment almost coincide (0.67 Å and 0.66 Å, respectively), which is also realized for compounds with Mo and Fe [11]. Therefore, the authors of [11] suggest using thin films to obtain an ordered distribution of elements. The B-site ordering double perovskites has also been widely reported in room-temperature electrolysis, such as water splitting [12].…”
Section: Introductionmentioning
confidence: 80%
“…It was shown that the decoupling of phonon-glass and electron-crystal behaviors in oxides is possible by reducing thermal conductivity due to the induced dipolar glassy state as a result of relaxor ferroelectricity [10]. It should be noted that the ionic radii of iron and niobium in a sixfold environment almost coincide (0.67 Å and 0.66 Å, respectively), which is also realized for compounds with Mo and Fe [11]. Therefore, the authors of [11] suggest using thin films to obtain an ordered distribution of elements.…”
Section: Introductionmentioning
confidence: 89%